2020
DOI: 10.1515/med-2020-0193
|View full text |Cite
|
Sign up to set email alerts
|

Culture-negative infective endocarditis (CNIE): impact on postoperative mortality

Abstract: AbstractIntroductionPoor postoperative outcomes have been reported after surgery for infective endocarditis (IE). Whether the absence of positive cultures impacts the prognosis remains a matter of discussion. The aim of this study was to evaluate the impact of negative cultures on the prognosis of surgically treated IE.MethodsThis was a single-center, retrospective study. From Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Of note, the impact of treatment modality (surgery vs. medical treatment alone) was seldom taken into account in previous series. 6 , 7 , 9 , 11 , 16 , 18 In the present study, advanced disease possibly discouraging the use of surgery because of absolute/relative contraindications was more frequently observed in CNIE than CPIE patients. All of this is in line with the fact that CNIE patients with theoretical surgical indications were less frequently operated upon than CPIE patients.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Of note, the impact of treatment modality (surgery vs. medical treatment alone) was seldom taken into account in previous series. 6 , 7 , 9 , 11 , 16 , 18 In the present study, advanced disease possibly discouraging the use of surgery because of absolute/relative contraindications was more frequently observed in CNIE than CPIE patients. All of this is in line with the fact that CNIE patients with theoretical surgical indications were less frequently operated upon than CPIE patients.…”
Section: Discussionsupporting
confidence: 45%
“…According to some series, CNIE is not associated with increased early mortality, 6,9,18 whereas others suggest a relevant, unfavourable impact on early and/or long-term mortality. 7,11,16 In our series, 30-day mortality was approximately 5% higher in CNIE than CPIE patients. Notably, although the direction of the effect was towards increased mortality, CNIE did not turn out to be a predictor at 30 days at stepwise multivariable analysis but was associated with 30-day mortality at LASSO regression.…”
Section: Culture-negative Infective Endocarditis Characteristics and ...mentioning
confidence: 44%
See 1 more Smart Citation
“…The frequency of culture-negative IE was similar in women and men in our study but was overall higher (27.5%) when compared to the findings of the European endocarditis registry, which reports a frequency of 21% [ 3 ]. A recent study by Salsano et al [ 31 ] showed that culture-negative IE is associated with a significantly higher adjusted postoperative risk for early mortality. Culture-negative IE may complicate treatment and result in a worse outcome, as observed in our male patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with higher morbidity and mortality than blood culture-positive endocarditis [3] . Previous studies also described that BCNIE was associated with a higher frequency of heart failure and valve perforation; furthermore, even surgically treated BCNIE is associated with a higher incidence of multiorgan failure, postoperative heart failure, and in-hospital mortality [4] , [5] .…”
Section: Discussionmentioning
confidence: 90%